Challenges in Type 2 Diabetes Prevention among Senior High School Students: A Qualitative Study - Nila Kusumawati; Syafrisar Agritubella; Alice Rosy; Fitry Erlin; Hanno Pijl (Shiraz University of Medical Sciences, 2024)
Background: Schools, a place where students spend much more time than home, play an important role in preventing the nation's future generation from type 2 diabetes mellitus (T2DM). This study aimed to explore challenges in T2DM prevention among senior high school students.Methods: The study was conducted in Riau Province, Indonesia, from June to August 2023 using a qualitative content analysis. 31 respondents, determined by data saturation, were recruited using purposeful sampling. They were public senior high schools' principals, vice principals, school health services staff, school canteen tenants, students, parents, and primary health care personnel in six districts. Data were collected through semi-structured face-to-face interviews and document review. Graneheim and Lundman's content analysis method was used to analyze the data in Nvivo version 11 software. The Lincoln and Guba Qualitative research criteria for trustworthiness were used to ensure the rigor of the study.Results: The main concepts obtained from the data were classified into three themes entitled, "Nonoptimal existing diabetes prevention programs in schools", "Inadequate knowledge of school community on T2DM", and "Inadequate policies to prevent diabetes in schools"Conclusion: An evidence-based, well-organized, and systematic school-based diabetes prevention program is fundamental to help overcome challenges and prevent future T2DM incidence. It requires relevant stakeholders' high level of awareness, strong collaborations with the school community, and effective school policies.